One-Dimensional Beam Scanning Transmitarray Lens Antenna Fed by Microstrip Linear Array - Na Kou; Shixing Yu; Zhao Ding; Zhengping Zhang (IEEE Access, 2019)
This paper proposed a one-dimensional beam scanning transmitarray lens antenna fed by a microstrip linear array antenna which owns a wide pattern in the plane orthogonal to the array axis and a narrow pattern in the plane that includes the array axis. The design principle of transmitarray lens aims to modulate a fan beam into a pencil beam by compensating phase shift of the linear array on the plane orthogonal to the array axis at X band. First, the Rotman lens feed network is used to implement nearly ±40° one-dimensional beam scanning for the linear array with 1 × 8 microstrip antenna elements. Then, a lowprofile transmitted element with only one-layer of the substrate is utilized to design the new transmitarray lens, which can reduce fabrication expense and difficulties. After adding the transmitarray lens, maximum gain increments of 7.81 and 7.65 dB in simulation and measurement can be obtained in quasi-boresight directions, and gain increment could be obtained within ±25° beam scanning range. Besides, the fan beams of the original linear array are smoothly transformed into pencil beams.